Crisis Tendencies in Household Savings in the Countries with Developed Market Economy and Russia - A. Kostomarova (Vestnik MGIMO-Universiteta)
The article looks at the dynamics of household saving rates and savings in terms of numbers in some of the leading world economies during the current economic crisis, makes comparative analysis with Russia. The author examines the reasons for changes in peoples’ behavior during crisis, including the influence of pessimistic opinion regarding expenses and savings, underlines a growing role of savings «for a rainy day», describes the model of consumption behavior.